The impact on the implementation of E-commerce in the strategic management of a Mype in Los Olivos 2022 - Jimenez-Paredes, Edita; Meneses-Claudio, Brian; Rios-Rios, Segundo (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Nowadays Mypes companies have begun to use E-commerce platforms or e-commerce, for most entrepreneurs who conducted their business, they had great advantage in increasing their sales. Because, it allowed them to attract more customers than expected to their businesses, since the networks allowed them to stay in connectivity with their customers, that is to say, they were able to expand nationally. Therefore, the research work proposes to describe the relationship between e-commerce or electronic commerce with companies. The result was a positive impact because social networks have become a trend for companies and have generated economic growth in them. As a conclusion, it has been identified the great importance of using digital platforms. Because it generates facilities of how to acquire their products without the need to go to physical stores, but to take it to your home.